Integrated Task-Based Learning: Sebuah Alternatif Teknik Peningkatan Kompetensi Bahasa Inggris pada SMK Permesinan - Yuliana, Y. Gatot Sutapa (Universitas Tanjungpura, 2016)
Dealing with the demands of developing job opportunities, and the importance of English language competence to meet the communication needs in the global industrial business, SMK (Senior Higher Vocational School)is expected to create medium-level â€œengineersâ€who are ready to work, adapt and fulfil the industries ownerâ€™s requirements. In the miniature of industrial settings the students were educated and prepared to be adopted directly by industries. Therefore, the quality, relevance of education and vocational curriculum are framed with adaptive competence in English directed in accordance with local needs and employment opportunities of the industries provided both nationally and internationally. With highly requiring the English Language Competency, industry, business, society and governent areplacing themselves as the most important factors determining the relevance judgments which are kept in the vocational education.To be skilful and communicative aremostly expected by the whole or a large part of the public to endorse the vocational readiness to be appropriate with the business world. This will also bring SMK to be economic assets that is essential, prospective,and therefore able to support the general welfare and go public.